(untitled) (Baghdad Science Journal, 2024)
This work shows a new analytical method (ion pair HPLC) for the analysis of Bisoprolol Fumarate (BIS) and Carvedilol (CAR) in bulk and tablet. The developed analytical method has been carried out on an Inertsil ODS-3 5µL column 4.6 X 250 mm (w), as stationary phase using a mobile phase Acetonitrile/ water 50/50 (v/v) containing sodium heptane sulfonic salt 0.001M as Ion pair agent. The detection wavelength was 223 nm and the flow rate was 1.5 mL /min. Retention times were 3.5 min of BIS and 5.8 min of CAR. The analytical method has been validated by ICH guidelines. The developed method gave linearity in the concentration range of 20–60 µg/ mL accuracy with mean recovery values between 98-102 % (99.73% for BIS and 101.2% for CAR). The developed method is useful for separating and determining Bisoprolol Fumarate and Carvedilol in their pharmaceutical forms.